Biosynthesis of Rubber in Cultured Cells of Sonchus oleraceus - Uesugi, Akari; Kuroda, Satoshi; Hosokawa, Tomohiro; Inoue, Yukino-Miyagi; Ohya, Norimasa (Asian Journal of Chemistry, 2013)
Rubber (cis-1,4-polyisoprene) was detected in the leaves of Sonchus oleraceus by 1H-nuclear magnetic resonance spectroscopy. The rubber had a low molecular weight with a narrow molecular weight distribution centered around 1.0 × 105 Da. Callus cultures were initiated from the leaf parts of S. oleraceus and suspension cultures were established in Murashige and Skoog's medium with various concentrations of 1-naphthalene acetic acid (NAA) and benzylaminopurine (BA). The cell biomass was higher in the presence of 1-naphthalene acetic acid (0.1 mg/L) and benzylaminopurine (0.1 mg/L). The cultured cells contained trace amounts of rubber-like polymer identified by gel permeation chromatography.